Scallop-shaped p-type FinFETs with improved short-channel effects immunity and driving current. (15th March 2022) - Zhang, Zhaohao; Gan, Weizhuo; Li, Junjie; Kong, Zhenzhen; Han, Yanchu; Liu, Yang; Wang, Guilei; Wu, Zhenhua; Yu, Jiahan; Zhang, Qingzhu; Xu, Gaobo; Zhang, Yongkui; et al.
Abstract: In this work, scallop-shaped p -type fin field-effect transistors (S-FinFETs) that outperform control-FinFETs for a given gate length are fabricated based on a conventional high-к metal gate FinFET fabrication flow. Because of the scallop-shaped gate structure and ultra-thin (∼5 nm) S-fin channel, the S-FinFETs demonstrate a 25% improvement in subthreshold swing and a 54% decrease in drain-induced barrier lowering compared with those of the control-FinFETs for a 20 nm physical gate length. Furthermore, a driving current of 200 μA/μm is obtained for S-FinFETs with a source/drain epitaxial substrate and a gate length of 20 nm, matching the performance of control-FinFETs with a source/drain epitaxial substrate. With improved short-channel effect immunity, the proposed S-FinFET provides a promising candidate beyond-FinFET technology.